Commodity as a science and its development in Europe - Hlusova, Anastasia (My University, 2014)
Herbals and pharmacopoeia written by medieval monks in monasteries may be regarded as early roots for commodity science, describing carefully pharmaceutical drugs, their healing and toxic effects and falsifications. Later this early branch of commodity science focused more and more on food. Modem codices, e.g. for food, might be interpreted as successors of these early books of commodity
Keywords: commodity; development; science; товар; розвиток; наука; развитие